Image-Guided Percutaneous Drainage of Abdominal Abscesses in Pediatric Patients - Dimitrij Kuhelj; Crt Langel (MDPI AG, 2024)
Image-guided percutaneous abscess drainage (IPAD) is an effective, minimally invasive technique to manage infected abdominal fluid collections in children. It is the treatment of choice in cases where surgery is not immediately required due to another coexisting indication. The skills and equipment needed for this procedure are widely available. IPAD is typically guided by ultrasound, fluoroscopy, computed tomography, or a combination thereof. Abscesses in hard-to-reach locations can be drained by intercostal, transhepatic, transgluteal, transrectal, or transvaginal approaches. Pediatric IPAD has a success rate of over 80% and a low complication rate.